Selective N-alkylation of aniline with methanol over a heteropolyacid on montmorillonite K10 - Nehate, Manoj; Bokade, Vijay V. (Applied Clay Science, 2009)
N-methylaniline is an industrially important product in the manufacture of paper, textile dyes, drugs, perfumes and explosives. The vapour phase alkylation of aniline with methanol forming N-methylaniline is advantageous over liquid phase alkylation. In present study, vapour phase methylation of aniline over dodecatungestophosphoric acid supported on K10 montmorillonite was systematically studied and optimization of process parameters was carried out. The 20% m/m DTPA/K10 was found to be optimum with 79% aniline conversion and 99% N-methylaniline selectivity. The reaction required milder operating conditions than reported for commercial catalysts. We also studied the feasibility of 20% m/m DTPA/K10 as a catalyst for the alkylation of aniline with other alcohols like ethanol, n-propanol, iso-propanol and n-butanol. The activity of 20% m/m DTPA/K10 decreased with increasing carbon number. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Alkylation; Aniline; Heteropolyacid; montmorillonite K10; N-methylaniline